HP and EBVaGC in Peruvian patients - Lopez, CB (2018)
Gastric cancer (GC) is the second most common cancer and first leading cause of cancer-related deaths in Peru. Infection by Helicobacter pylori (HP) and Epstein-Barr virus (EBV) are accepted carcinogenic and infection is widely spread in the Peruvian population. The aims of this study were to evaluate HP and EBV-associated GC (EBVaCG), to assess the prevalence rate and to define the characteristics of Peruvian patients. GC samples were prospectively collected from patients who underwent gastroscopy or surgical resection with no preoperative treatment at INEN between 2015 and 2017. Tumor tissue (T), proximal healthy tissue (P) and distal healthy tissue (D) samples were assessed for HP and EBV by quantitative PCR (qPCR) using specific primers. HP and EBV status were analyzed along with clinicopathologic parameters of the tumor. Kaplan-Meier estimation curves overall survival (OS) was applied. Comparison between qPCR detection and current standard methods of detection was also performed. All tests were two sided, and a p≤0.05 was considered statistically significant.